Fracture zones in the Mid Atlantic Ridge lead to alterations in prokaryotic and viral parameters in deep-water masses - Simone Muck (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Thomas Griessler (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Nicole Köstner (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Adam Klimiuk (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Christian Winter (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Gerhard J. Herndl (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna) (Frontiers in Microbiology, 2014)
The abstract is available here: https://uscholar.univie.ac.at/o:467115 The abstract is available here: https://uscholar.univie.ac.at/o:467115